Pillar capital, triple-arched gateway - Ghosh, Ayan (2023)
Corinthian order pillars with elaborate floral capitals decorated with acanthus leaves and scrolls, stand at the corners of the triple-arched gateway. The gateway was sponsored by Rustomjee Jamsetjee Jeejeebhoy (1824-72) and designed by William Tracey, though the building was completed by Messrs. Scott, McClelland and Co. after Tracey's untimely death.